5-Aminolevulinic Acid False-Positive Rates in Newly Diagnosed and Recurrent Glioblastoma: Do Pseudoprogression and Radionecrosis Play a Role? A Meta-Analysis - Ricciardi, Luca; Sturiale, Carmelo Lucio; Scerrati, Alba; Stifano, Vito; Somma, Teresa; Ius, Tamara; Trungu, Sokol; Acqui, Michele; Raco, Antonino; Miscusi, Massimo; Della Pepa, Giuseppe Maria (Frontiers in Oncology, 2022)
Background Several studies have confirmed the impact 5-aminolevulinic-acid (5-ALA) on extent of resection in newly diagnosed glioblastoma (GBM). However, there controversies on the 5-ALA fluorescence status in recurrent GBM surgery, with specific reference to pseudoprogression or radionecrosis; therefore, the safety and the accuracy of surgical planning in 5-ALA assisted procedures in the recurrent context is still unclear. Materials and methods This is a systematic review and meta-analysis, consistently conducted according to the PRISMA statement. Comparative studies on 5-ALA use in newly diagnosed and recurrent glioblastoma have been identified, and data on fluorescence status, and correlations between fluorescence status and histological findings. We performed meta-analyses of proportions to estimate the pooled rates of each outcome. Results Three online medical databases (PubMed, Scopus, Cochrane Library) were screened, 448 articles were evaluated, and 3 papers were finally included for data analysis. Fluorescence rate was not difference between newly diagnosed and recurrent GBM (p=0.45;OR:1.23;CI:0.72–2.09;I2=0%), while the rate of 5-ALA fluorescence positive areas not associated to histological findings of GBM cells was higher in recurrent GBM (p=0.04;OR:0.24;CI:0.06–0.91;I2 = 19%). Furthermore, there were no cases of radionecrosis in false positive samples, while inflammation and signs of pseudoprogression were found in 81.4% of the cases. Discussion and conclusions Therefore, a robust awareness of 5-ALA potentialities and pitfalls in recurrent GBM surgery should be considered for a cognizant surgical strategy. Further clinical trials could confirm the results of the present meta-analysis.